2008
DOI: 10.1088/0022-3727/41/19/194002
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown, scaling and volt–ampere characteristics of low current micro-discharges

Abstract: We give preliminary results on the breakdown and low current limit of volt-ampere characteristics of simple parallel plate non-equilibrium dc discharges at standard (centimetre size) and micro-discharge conditions. Experiments with micro-discharges are reported attempting to establish the maintenance of E/N, pd and j/p 2 scalings at small dimensions down to 20 µm. It was found that it may not be possible to obtain properly the left-hand side of the Paschen curve. The possible causes are numerous but we believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 25 publications
5
53
1
Order By: Relevance
“…Paschen curve, should be the same for all electrode gaps unless processes that void scaling take place. In micro-discharges, apart from well known processes that cause violation of scaling (gas and electrode heating, stepwise processes and three-body collisions at high pressures), one may expect processes such as field emission and quantum tunnelling of electrons [24]. .…”
Section: Properties Of Micrometer Size Discharges -Scaling Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paschen curve, should be the same for all electrode gaps unless processes that void scaling take place. In micro-discharges, apart from well known processes that cause violation of scaling (gas and electrode heating, stepwise processes and three-body collisions at high pressures), one may expect processes such as field emission and quantum tunnelling of electrons [24]. .…”
Section: Properties Of Micrometer Size Discharges -Scaling Lawsmentioning
confidence: 99%
“…to take into account effective area covered by the discharge, which may be considerably smaller than the area defined by the electrode diameter [25]. Micro-discharges operate at pressures higher than pressures used in standard size discharges, so that the occurrence of constriction in micro-discharge is even more pronounced [24]. Therefore, it is essential to record radial profiles of emission.…”
Section: Properties Of Micrometer Size Discharges -Scaling Lawsmentioning
confidence: 99%
“…Charge neutrality and discharge structure are relatively unchanged down to gaps of ∼100 µm [31,32]. We have investigated the dc breakdown and current characteristics of various PP structures and have tested pd and j/p 2 scaling for gaps of a few millimetres down to 20 µm [12,13,33]. Low pressure conventional hollow cathodes (CHCs) have a complicated dependence on various discharge parameters and have been extensively studied [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…At ( pd ) < ( pd ) min , however, we are restricted because the SEE investigations are required for a detailed study in the breakdown regime at lower pressures (see Refs. for details). If ( pd ) < ( pd ) min occurs, the breakdown corresponds to the higher applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the strong DC fields give notable supports for both the ion current toward the cathode and the development of the electron‐induced ionization. In the low‐current microplasmas, Petrović et al determined the behavior of the Paschen curves with pd and j / p 2 scaling ( d is discharge gap and j is current density) in the range of micrometer scales when only the electrons emitted by the surface with bombardment process are important. However, it can be observed for effects of photons that the γ levels remarkably approach the high values during the development of the photoionization structure .…”
Section: Introductionmentioning
confidence: 99%